2016
DOI: 10.1038/nmicrobiol.2016.227
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Integrated multi-omics of the human gut microbiome in a case study of familial type 1 diabetes

Abstract: © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A previous study, published in 2016, sets the stage for larger-scale metagenomics studies by demonstrating, on a smaller-scale, how specific gastrointestinal microbial communities and host-microbe phenotypic relationships are associated with onset of human disorders (18). Although the role of exocrine pancreas function in T1D onset remain unclear, they showed that exocrine pancreas enzymes, including amylase, carboxypeptidase CPA1 and CUZD1are less abundant in T1D patients (18). These initial results are promising and provides the field with an initial insight into how the T1D metaproteome differs in functionality compared to controls.…”
Section: Gut Proteomementioning
confidence: 99%
See 1 more Smart Citation
“…A previous study, published in 2016, sets the stage for larger-scale metagenomics studies by demonstrating, on a smaller-scale, how specific gastrointestinal microbial communities and host-microbe phenotypic relationships are associated with onset of human disorders (18). Although the role of exocrine pancreas function in T1D onset remain unclear, they showed that exocrine pancreas enzymes, including amylase, carboxypeptidase CPA1 and CUZD1are less abundant in T1D patients (18). These initial results are promising and provides the field with an initial insight into how the T1D metaproteome differs in functionality compared to controls.…”
Section: Gut Proteomementioning
confidence: 99%
“…A plethora of studies have demonstrated that the human microbiome has the potential to affect the pathogenesis of immune diseases, particularly autoimmune diseases in which the immune system fails to distinguish self from non-self proteins and attacks self-tissues. Examples of such diseases include multiple sclerosis (8), rheumatoid arthritis, systemic lupus erythematosus, anti-phospholipid syndrome (10), Crohn's disease (11)(12)(13), ulcerative colitis (14), inflammatory bowel diseases (15,16), coeliac disease (17), and Type 1 Diabetes (T1D) (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fate of these microbial consortia in the face of perturbations is often not understood nor predictable (Muller, 2019). Longitudinal approaches are necessary to understand microbial community dynamics, as they may offer valuable insights into temporal trends and consequences of environmental forcings, when used in tandem with host-derived (Heintz-Buschart et al, 2016;Lloyd-Price et al, 2019;Mars et al, 2020) or environmental (Law et al, 2016;Herold et al, 2020) data. Longitudinal studies can be conducted using diachronic or synchronic approaches (Costa Junior et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Core Operational Taxonomic Units (OTUs), based on 16S rRNA gene amplicon libraries have been reported as being present in diverse anaerobic communities (Rivière et al, 2009;Huse et al, 2012;Rui et al, 2015;Calusinska et al, 2018). Core microbial communities can be more precisely identified by the combination of read-based and binning metagenome techniques (Nolla-Ardèvol et al, 2015a;Campanaro et al, 2016Campanaro et al, , 2018aHeintz-Buschart et al, 2016;Stolze et al, 2016;Treu et al, 2016;Zhu et al, 2018). Metagenomics studies also allow for the extrapolation to ecological functional networks (Schlüter et al, 2008;Wirth et al, 2012;Campanaro et al, 2016;Stolze et al, 2016), although this is of limited information, because the abundances of genes coding for enzymes do not necessarily reflect biological activity (De Vrieze et al, 2016).…”
Section: Introductionmentioning
confidence: 99%